SISTEM DAN PROSEDUR PENCAIRAN DANA LANGSUNG (LS) PADA BADAN PENYULUHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PERTANIAN KEMENTERIAN PERTANIAN REPUBLIK INDONESIA - Rizky Lahmudin Abdjul (2020)
The Field Work Practice (PKL) activity aims to develop the ability of students to apply the theory learned in class in practice that occurs in the world of work. This Field Work Practice was carried out of 3 months at the Ministry of Agriculture Republic Indonesia precisely at the Agriculture Human Resource Development and Counseling Agency (BPPSDMP) by conducting interviews and direct obeservations at the departmental departments related to direct fund disbursement (LS) to obtain relevant information related to the Ministry of Agriculture Republic Indonesia. Direct Fund Disbursement is the process of disbursing funds carried out by the KPPN to entitled parties or partners based on SPM-LS issued by the PA/PA Authority on behalf of the entitled parties in accordance with valid proof of expenditure. Disbursement of funds is very important because the funds are used to finance various operational acitivities of work units. The study aims to determine the process that occurs when direct funds disbursement according to procedure or not. By implementing these procedures that are integrated with the State Budget Treasury System the process of disbursement funds runs better and is very thorough. Therefore technical guidance to word units is needed regarding the SPM submission format for disbursing funds. The technical guidance aims to be able to minimize filing errors so that the process of disbursing funds will not be hampered.